PENGGUNAAN MEDIA TAYANGAN FILM PENDEK DALAM PEMBELAJARAN MENYUSUN KEMBALI TEKS CERITA PENDEK SECARA LISAN DENGAN METODE SIMULASI PADA SISWA SMP - Fatmawati, Aristia (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Short film display media is an innovative media that can be used to improve students' competence in learning to re-arrange short story text orally. The purpose of this research is to describe the use of short film display media in learning to reset short story text orally with simulation method for junior high school students. Data were collected by test and non-test methods. Data obtained through two activities namely pretest and posttest. The data is obtained from students of class VII of SMP N 2Blora. The results of the use of short movie display media in the learning re-compile the text of short stories orally with the simulation method of junior high school students is quite influential. Evidently there is a difference between before and after treatment. Before the average pretest value of knowledge was 77.28. However, at posttest, the average value of knowledge becomes 85.81. For skill, when pretest, the average value is 75.63, but when the posttest becomes 83.45.